(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Water is an essential component of all living organisms. Portable water is essential to humans, animals, plants and other life forms despite providing no calories and no organic nutrients. Water is helping the growth and development of living organisms. Water is also used for all types of daily routines. The present study is on the preliminary physicochemical analysis of pond water in the Raipur area. The samples were taken from the various places of Raipur city ponds, such as Aama Talab, Bhanpuri, Datrega, Daldal Seoni, Urla ponds for preliminary analysis of physicochemical. The collected samples were analyzed for the parameters like Temperature, pH, TDS, Chloride, Alkalinity, Hardness, Ca, Mg, Biological Oxygen Demand (BOD), Chemical Oxygen Demand (COD) and Dissolved Oxygen (DO). The comparative investigation of physicochemical characteristics of water samples with the BIS standard parameters shows that the improvement of water quality parameters should be carried out periodically to develop the water sources.